Synergistic antifungal activity of sodium hypochlorite, hydrogen peroxide, and cupric sulfate against penicillium digitatum - Cerioni, Luciana (2009)
Oxidizing compounds such as sodium hypochlorite (NaCIO) and hydrogen peroxide (H2O2) are widely used in food sanitization because of their antimicrobial effects. We applied these compounds and metals to analyze their antifungal activity against Penicillium digitatum, the causal agent of citrus green mold. The MICs were 300 ppm for NaCIO and 300 mM for H2O2 when these compounds were individually applied for 2 min to conidia suspensions. To minimize the concentration of these compounds, we developed and standardized a sequential treatment for conidia that resulted in loss of viability on growth plates and loss of infectivity on lemons. The in vitro treatment consists of preincubation with 10 ppm of NaCIO followed by incubation with 100 mM H2O2 and 6 mM CuSO4 (cupric sulfate). The combination of NaCIO and H2O2 in the presence of CuS04 produces a synergistic effect (fractional inhibitory concentration index of 0.36). The sequential treatment applied in situ on lemon peel 24 h after the fruit was inoculated with conidia produced a significant delay in the fungal infection. The in vitro treatment was effective on both imazalil-sensitive and imazalil-resistant strains of P. digitatum and Geotrichum can-didum, the causal agent of citrus sour rot. However, this treatment inhibited 90% of mycelial growth for Penicillium italicum (citrus blue mold). These results indicate that sequential treatment may be useful for postharvest control of citrus fruit diseases. Copyright ©, International Association for Food Protection.